Comparative analysis of nasal endoscopic and radiological findings in chronic rhinosinusitis patients - Kagathara, Virali Prabhulal; Mahajan, S. B.; Rathi, Abhinav; Gangwar, Navneeta; Bhardwaj, Viny (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Chronic rhinosinusitis (CRS) is a complex inflammatory disorder causing significant reduction in quality of life and interfere in day to day activity. Accurate diagnosis is crucial for effective management, typically involving nasal endoscopy and CT imaging to assess the extent of sinus involvement. Methods: This prospective observational study was conducted at Jaipur national university institute of medical sciences and research centre from July 2022 to May 2024. It included 75 patients diagnosed with CRS. Subjective quantification of disease was done using SNOT-22 scoring system. Diagnostic evaluations were performed using nasal endoscopy and CT scans, with findings scored according to the Lund-Kennedy and Lund-MacKay systems. Results: The study highlighted a strong correlation between endoscopic and CT findings, with Pearson correlation coefficients of 0.892 and 0.909 for endoscopic vs. SNOT-22 scores and CT vs. SNOT-22 scores, respectively. Discrepancies between the two diagnostic tools were also noted, emphasizing their complementary roles in CRS management. Conclusions: Integrating nasal endoscopy and CT imaging provides a robust framework for diagnosing and managing CRS, allowing for a detailed assessment of both mucosal and anatomical changes. The combined use of these tools enhances the ability to tailor treatment plans effectively.